Memory T cells specific to citrullinated α-enolase are enriched in the rheumatic joint. (August 2018) - Pieper, Jennifer; Dubnovitsky, Anatoly; Gerstner, Christina; James, Eddie A.; Rieck, Mary; Kozhukh, Genadiy; Tandre, Karolina; Pellegrino, Sara; Gebe, John A.; Rönnblom, Lars; Sandalova, Tatyana; Kwok, William W.; et al.
Abstract: ACPA-positive rheumatoid arthritis (RA) is associated with distinct HLA-DR alleles and immune responses to many citrullinated self-antigens. Herein we investigated the T cell epitope confined within α-enolase326-340 in the context of HLA-DRB1*04:01 and assessed the corresponding CD4 + T cells in both the circulation and in the rheumatic joint. Comparative crystallographic analyses were performed for the native and citrullinated α-enolase326-340 peptides in complex with HLA-DRB1*04:01. HLA-tetramers assembled with either the native or citrullinated peptide were used for ex vivo and in vitro assessment of α−enolase-specific T cells in peripheral blood, synovial fluid and synovial tissue by flow cytometry. The native and modified peptides take a completely conserved structural conformation within the peptide-binding cleft of HLA-DRB1*04:01. The citrulline residue-327 was located N-terminally, protruding towards TCRs. The frequencies of T cells recognizing native eno326-340 were similar in synovial fluid and peripheral blood, while in contrast, the frequency of T cells recognizing cit-eno326-340 was significantly elevated in synovial fluid compared to peripheral blood (3.6-fold, p = 0.0150). Additionally, citrulline-specific T cells with a memory phenotype were also significantly increased (1.6-fold, p = 0.0052) in synovial fluid compared to peripheral blood. The native T cell epitope confined within α-enolase326-340 does not appear to lead to complete negative selection of cognate CD4 + T cells. In RA patient samples, only T cells recognizing the citrullinated version of α-enolase326-340 were found at elevated frequencies implicating that neo-antigen formation is critical for breach of tolerance. Graphical abstract: Highlights: Antibody responses to citrullinated proteins are common in RA and associate to HLA-DR alleles. Citrullinated peptides can be presented to T cells on HLA-DR. Alpha-enolase peptide 326–340 binds HLA-DRB1*04:01 in both its native and citrullinated form. Crystal structures demonstrate the citrulline/arginine protruding towards the TCR contact area. HLA-DR tetramer staining showed elevated frequencies of cit-specific T cells in the RA joint.